Completing the Jigsaw: The Recent Development of the Maritime Boundaries in the Timor Sea - Ramon, Adrianus Adityo Vito (Indonesian Journal of International Law, 2018)
The research argues that recent events, including the independence of Timor-Leste and the positive outcome of the Timor-Leste – Australia compulsory conciliation proceeding have provided Indonesia with political as well as, potentially legal basis to strive for the negotiation of its maritime boundary in the vicinity of Timor Sea with Timor-Leste as well as to pursue for the renegotiation of the 1997 Perth Treaty between Indonesia and Australia (yet to be entered into force) as the area that being delimited by the said treaty currently encompassed the maritime area of Timor-Leste. The research furthermore argues that a similar condition had also occurred for the other coastal states in the vicinity of Timor Sea (Australia, and Timor-Leste). The series of events between the coastal states of Timor Sea have arguably provided those coastal states with a perfect and timely setting to strive for the conclusion of its maritime delimitation dispute and therefore completing the jigsaw of maritime boundaries in the Timor Sea.